Impact of Good Nurse- Pharmacy Communication in Achievement of Excellent Care - Zahra Ali Al Zaid,; Khadijah Hassan Alhammadi,; Naif Sallam Ahmed Albariqi,; Fatmah Ahdal Khardli,; Halimah Mohammed Ahmed Zaila,; Roaa Zaylaee Hussain Alawi,; Najwa Arar Hadwer,; Turki Talae Ali Almangahi,; Adel Saeed Al Zahrani,; Ohud Mohammed Jabril Mohammed, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Effective communication between nurse- pharmacy is essential for fostering a supportive working environment, enhancing patient safety, and improving healthcare outcomes. Poor communication is a significant contributor to sentinel events and adverse incidents in healthcare, particularly in nursing contexts. This study explores the relationship between nurse- pharmacy communication satisfaction and patient safety culture, focusing on the impact of communication satisfaction on safety culture perceptions and practices in hospital settings. Methods: A cross-sectional study was conducted using a proportional random sampling method to collect data from nurse- pharmacy working in four medical/surgical units. Nurse- pharmacy who had worked in the hospital for at least two months, provided direct patient care, and worked over 7.5 hours weekly were included. The Communication Satisfaction Questionnaire (CSQ) and the Hospital Survey on Patient Safety Culture (AHRQ) were used to assess communication satisfaction and safety culture, respectively. Spearman’s Rank correlation test was used to analyze the relationship between the variables, with a significance level set at p<0.05. Results: A total of 51 nurse- pharmacy participated, with the majority (82.4%) aged 20-30 years and 76.5% being female. The study revealed a significant positive correlation between nurse- pharmacy communication satisfaction and the quality of patient safety culture (p=0.015, α=0.05, r=0.338). Nurse- pharmacy with higher communication satisfaction showed a better perception of patient safety culture, particularly in areas like teamwork, coordination, and collaboration with doctors. However, challenges like staffing issues and workload remained concerns for patient safety. Conclusion: The study found that communication satisfaction among nurse- pharmacy is significantly related to the quality of patient safety culture. Improving communication within healthcare teams is essential for fostering a positive safety culture, which can lead to better patient outcomes and reduced adverse events. Hospitals should prioritize enhancing communication practices to strengthen both nurse satisfaction and patient safety.